Erratum to: A study of vorticity formation in high energy nuclear collisions - F. Becattini; G. Inghirami; V. Rolando; A. Beraudo; L. Del Zanna; A. De Pace; M. Nardi; G. Pagliara; V. Chandra (European Physical Journal C: Particles and Fields, 2018)
Due to an oversight of ours in proofreading and a communication problem with the publisher, the figures published in F. Becattini et al. Eur. Phys. J. C (2015) 75: 406 were not correct. This Erratum contains the correct figures as in arXiv 1501.04468v2, submitted on March 12 2015, and the post-publication version arXiv 1501.04468v3, submitted on August 17 2015.